Assessment of retail outlet choice and shopping behaviour of fresh fruit and vegetable buyers in Davao City - Edig, Lourdes Angelie O.
The continued strenght in patronage of the traditional wet markets despite the presence of modern retail trade formats, the supermarkets, of Asian consumers has piqued the interest of researchers worldwide on the reasons behind this phenomenon. This study seeks to provide an assessment of the preferences of fresh fruit and vegetable (FFV) buyers in Davao City in choosing a retail outlet, their reasons behind this choice, and their subsequent shopping behaviour inside wet markets and supermarkets. One hundred ninety-two households in different baranggays were administered survey questionnaires to gauge their outlet choices, spending behaviour, frequency of shopping visits and the retail outlet attributes they considered in making their choices when buying FFV.Using the bivariate Tobit model analysis, FFV spending in wet markets was positively related to the product assortment available, the price of products and food safety concerns. On the other hand, FFV spending in wet markets was positively related to household income and price of products. The female members of the household are the main FFV shoppers and households generally purchase FFV once or twice a week and more so in wet markets. Wet market shoppers' top reason for choosing a retail outlet was that of cheaper price of products while supermarket shoppers' valued convenience and location advantage in choosing a retail outlet to patronize.